RoboCOP: A Robotic Coach for Oral Presentations - Trinh, Ha; Asadi, Reza; Edge, Darren; Bickmore, Timothy (Interactive, Mobile, Wearable, and Ubiquitous Technology (IMWUT), 2017)
Rehearsing in front of a live audience is invaluable when preparing for important presentations. However, not all presenters take the opportunity to engage in such rehearsal, due to time constraints, availability of listeners who can provide constructive feedback, or public speaking anxiety. We present RoboCOP, an automated anthropomorphic robot head that acts as a coach to provide spoken feedback during presentation rehearsals at both the individual slide and overall presentation level. The robot offers conversational coaching on three key aspects of presentations: speech quality, content coverage, and audience orientation. The design of the feedback strategies was informed by findings from an exploratory study with academic professionals who were experienced in mentoring students on their presentations. In a within-subjects study comparing RoboCOP to visual feedback and spoken feedback without a robot, the robotic coach was shown to lead to significant improvement in the overall experience of presenters. Results of a second within-subjects evaluation study comparing RoboCOP with existing rehearsal practices show that our system creates a natural, interactive, and motivating rehearsal environment that leads to improved presentation quality.